2021
DOI: 10.3389/fenvs.2021.763917
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Effects of the Herbicide Glyphosate on Plant, Animal and Human Health Through its Effects on Microbial Communities

Abstract: The herbicide glyphosate interferes with the shikimate pathway in plants and in major groups of microorganisms impeding the production of aromatic amino acids. Glyphosate application on plants results in a slow death, accelerated by reduced resistance to root pathogens. Extensive glyphosate use has resulted in increasing residues in soil and waterways. Although direct glyphosate effects on animals are limited, major concerns have arisen about indirect harmful side effects. In this paper, we focus on indirect e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 237 publications
(526 reference statements)
1
39
0
Order By: Relevance
“…Recently, we combined closely related bacterial species and different strains within species to identify changes in their sensitivity to glyphosate [ 7 ] under the microevolutionary perspective of Alignable Tight Genomic Clusters (ATGC) [ 22 ]. The study of the EPSPS enzyme showed that phylogenetic groups and bacterial lifestyle are key factors determining the intrinsic sensitivity to glyphosate, possibly resulting from thicker cell walls in addition to differences in EPSPS type [ 7 , 8 ]. Specifically, Firmicutes were significantly more resistant to glyphosate than the most sensitive Proteobacteria and Actinobacteria groups.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we combined closely related bacterial species and different strains within species to identify changes in their sensitivity to glyphosate [ 7 ] under the microevolutionary perspective of Alignable Tight Genomic Clusters (ATGC) [ 22 ]. The study of the EPSPS enzyme showed that phylogenetic groups and bacterial lifestyle are key factors determining the intrinsic sensitivity to glyphosate, possibly resulting from thicker cell walls in addition to differences in EPSPS type [ 7 , 8 ]. Specifically, Firmicutes were significantly more resistant to glyphosate than the most sensitive Proteobacteria and Actinobacteria groups.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a bacterial lifestyle was strongly associated with sensitivity, because facultative host-associated and parasitic bacteria are more sensitive to the herbicide than free-living bacteria. However, Van Bruggen et al showed that pathogens are generally less sensitive to glyphosate than host-associated and free-living bacteria, by analyzing literature data on minimal inhibitory concentrations for a large number of bacteria [ 8 ]. The microevolutionary analysis further revealed that bacteria may easily become resistant to glyphosate through small changes in the EPSPS active site in the short evolutionary time of ATGC with non-synonymous mutations and horizontal gene transfers [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature of the last ten years has focused on the medium and long-term effects of the persistence of organophosphates, revealing their toxicity and the serious impact on ecosystems of all environmental matrices (air, soil, rivers, sea) and consequently on the health of humans [ 1 , 2 ]. By contrast, related literature also reported conflicting results on the role of organophosphates in perturbing or modifying the activity and microbial composition in soil or water [ 3 , 4 , 5 ]. Glyphosate is one of the most used organophosphates in industrialized countries; it is a non-selective herbicide with broad-spectrum activity used to eliminate weeds in crops [ 6 ].…”
Section: Introductionmentioning
confidence: 99%